Effects of Market Orientation on the Overall Performance of Banks:A Field Study in the Skikda Region of Algeria - Belkebir, Boumediene; Bounab, Yacine (The Arab Journal of Administration, 2019)
According to the behavioral approach of Kohli and Jaworski in their three dimensions: information generation, information dissemination and response to information. The aim of this study is to examine the impact of market orientation on the overall performance of banks operating in Algeria, based on a twenty stat - It was distribute to a sample of 52 frames belonging to 11 banking agencies in the state of Skikda representing a number of banks operating in Algeria. The study concludedement that there is a statistically significant effect on the behavioral market orientation and its dimensions (generation or creation of information, dissemination of information, Information on the overall performance of the Skikda banking agencies, the results of this effect are weak due to the low level of market-oriented behavior of banking agencies.